Steamboat PROSPECTOR leaving Dawson for Whitehorse on the last trip of the season, Yukon Territory, Oct.19, 1905. - Peck, Odbur C.
Caption on image: "Last boat leaving Dawson for White Horse Oct 19, 1905." PH Coll 246.191 [Meed journal: "Steamer "Prospector" ready to leave Dawson for White Horse on the last trip of the season in October, 1905. The date by the photographer is inscribed Oct. 19th, but as the river was then choked full with ice, the departure was delayed by a few days. The boat fought against the ice and reached White Horse safely. The return voyage was started immediately thereafter and Dawson was reached just as the ice jammed there for the winter. ."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number